2019
DOI: 10.4049/jimmunol.1701649
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells Require Cell-Extrinsic and -Intrinsic TYK2 for Full Functionality in Tumor Surveillance and Antibacterial Immunity

Abstract: Tyrosine kinase 2 (TYK2) is a widely expressed receptor-associated kinase that is involved in signaling by a variety of cytokines with important immune regulatory activities. Absence of TYK2 in mice results in impaired NK cell maturation and antitumor activity, although underlying mechanisms are largely unknown. Using conditional ablation of TYK2 in NK cells we show that TYK2 is required for IFN-g production by NK cells in response to IL-12 and for an efficient immune defense against Listeria monocytogenes. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 83 publications
1
17
0
Order By: Relevance
“…The high susceptibility of Tyk2 −/− mice to lymphoid tumors is the result of an impaired tumor surveillance, in particular, a decreased cytotoxic capacity of NK/NKT and CTL cells [86,98]. The importance of TYK2 for NK cell-and CD8 + T cell-targeted tumor growth restriction was confirmed by studies with local tumor transplant models, using lymphoma (RMA-S and RMA-Rae1) and adenocarcinoma (MC38) cells [67,76,93]. Reduced CTL-dependent tumor cell killing is linked to impaired type I IFN signaling, although the mechanisms are elusive [98].…”
Section: Tyk2 and Immunity To Cancermentioning
confidence: 93%
See 4 more Smart Citations
“…The high susceptibility of Tyk2 −/− mice to lymphoid tumors is the result of an impaired tumor surveillance, in particular, a decreased cytotoxic capacity of NK/NKT and CTL cells [86,98]. The importance of TYK2 for NK cell-and CD8 + T cell-targeted tumor growth restriction was confirmed by studies with local tumor transplant models, using lymphoma (RMA-S and RMA-Rae1) and adenocarcinoma (MC38) cells [67,76,93]. Reduced CTL-dependent tumor cell killing is linked to impaired type I IFN signaling, although the mechanisms are elusive [98].…”
Section: Tyk2 and Immunity To Cancermentioning
confidence: 93%
“…IL-15 is dynamically regulated in the TME and enhances anti-tumor immunity [227,229,230]. We have shown that the absence of TYK2 in DCs results in reduced levels of IL-15Rα on DCs and macrophages in naïve mice ( [93] and see below). However, the nature of the TYK2-dependent signals that drive IL-15/IL-15Rα expression under homeostatic conditions is unclear.…”
Section: Il-15mentioning
confidence: 97%
See 3 more Smart Citations